Pengaruh Temperatur Panas Beton Terhadap Perubahan Fisik Dan Kuat Tekan Beton K-250 - ELYAS SUDRAJAD (Universitas Islam Lamongan, 2021)
Concrete is a material that has better fire / heat resistance than other materials. In this experiment using experimental methods in the laboratory using the applicable method.This research uses an oven to increase the heat temperature, the heating experienced in the concrete will result in changes in the basic properties of concrete. The purpose of this study was to determine the effect of hot concrete temperature on the compressive strength of K 250 concrete. The variations in temperature increase in this study were 1000C, 2000C, and 3000C. This study used a test object in the form of a cylinder with a diameter of 15 cm and a height of 30 cm. The results of the data obtained in this study are normal concrete 28 days that is 273.65 kg/cm2, 1000C 28 days is 149.09 kg/cm2, 2000C 28 days is 137.77 kg/cm2, 3000C 28 days is 122.67 kg/cm2..